THE MEANING OF BOLAANG MONGONDOW TRADITIONAL SONGS AND STUDENTS’ PERCEPTION ON THEM - Mega Yuniar Palit; Intama Jemy Polii; Viktory N. J. Rotty (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
The purpose of this research is to describe the meaning of the traditional songs of Bolaang Mongondow and the perceptions of students at SMP Negeri 2 Lolayan. This study employs a qualitative descriptive method, focusing on current issues. The gathered data is first organized, explained, and then analyzed. The data sources for this research are the students of SMP Negeri 2 Lolayan and a collection of three traditional songs from Bolaang Mongondow, namely Tano-tanobon, Moraoi and Tobatu Lipu. The data were collected by three steps; observation, interview and documentation. The result of the research showed that the majority of the students have good understanding of the meaning of Bolaang Mongondow traditional songs which they considered as the identity and reflection of Mongondow heritage. However, some students have a limited understanding due to various reasons such as insufficient learning time dedicated to Bolaang Mongondow traditional songs or a lack of proficiency in the Mongondow language. Furthermore, it is found that the songs have meanings. Tano-tanobon means to heed parental advice, love and cherish parents, and not hurt their feelings to lead a happy life. Moraoi means that Indonesia is known for its natural beauty from Sabang to Merauke, and similarly, Bolaang Mongondow possesses beautiful landscapes, rich flora and fauna, and hospitable communities. Lastly, Tobatu Lipu means someone who has ventured far still holds their birth land dear in their heart.